Determinación de la densidad critica en suelos inceptisoles y entisoles, aplicada al cultivo de fréjol phaseolus vulgaris l - Azuero Azansa, Cristhian Marco (2017)
Soil compaction is restrictive in agricultural production by that critical levels of soil density is considered to be of greater interest to continue to have normal conditions of their productive capacity in the crops, as evidenced in the present investigation that has been emphasized in determine the density criticizes in soils Inceptisols and Entisols applied to the cultivation of beans, distinguishing the effect of compaction compared the behavior of the plant in different levels of densities, with this problem raised the following objectives; assess the variation of density criticizes soils Inceptisols and Entisols depending on the increase of the density of the soil in the cultivation of beans; determine the variation of the resistance to The ground penetration inceptisol and entisol depending on the increase of the density of the soil; establish the soil density criticism about the roots of plants beans. To this end were prepared 60 cylinders PVC with the measures of 160 cm in diameter and 15 cm high, there compactaron soil inceptisol and entisol to 5 levels of densities 1,1; 1,2; 1,3; 1,4 and 1,5 g cm-3 sowing a seed of beans in each treatment in five repetitions, maintaining the substrate to field capacity under drip irrigation system, in which it is evaluated stages vegetative and reproductive plants in function of the various compacts and its dynamics of resistance to the penetration was taken using a penetrometer, by measuring their resistance before planting and during the development of the crop, showing that the soil inceptisol is compact more with an average Of resistance of 0.974 kg cm-2 due to the increase of the density of the soil and its texture clay and silt being likewise productive, while the ground entisol was obtained an average in levels of compaction of 0.642 kg cm-2 noting in addition that from the density of 1.3 g cm-3 the resistance to the penetration was 0.85 kg cm-2 the root mass, which was restricted which affects in a water deficit for cultivation as a lack of permeability of water and air circulation in the subsoil and by its homogeneity of compaction caused by the very high densities as 1.4 and 1.5 g cm-3, in such a way that the mean of the results of The variables are critical from the values set as the height of the plant (69.45 cm), length of the scabbard (12.10 cm), number of pods (6,1) and grains (54.3), moisture content in: stem (41.76 %), sheets (30.9 %), roots (8.77 %), pods (40.1%), grains (31.62 %) and root relationship/canopy (0.156). This last one stated of the derivation of moisture content of all the green area of the plant (leaves, flowers and fruits). The results identified it can be concluded that the soil density critical in soils Inceptisols and Entisols was 1.3 g cm-3 determined that values greater than this had a negative impact on the roots, affecting the development of the crop and thus to their productivity, the resistance to the penetration is a good indicator of the compaction caused by intrinsic and extrinsic factors that cause negative effect on crop production of beans. The ground entisol resulted to be unproductive in all densities due to its sandy texture.